Uma aurora, um crepúsculo – imagens da juventude estudantil da UFG no período final da ditadura militar: um jogo de poderes? - Ribeiro, Itamar Pires (2017)
The main objective of this research is to produce a documentary that has as theme the experience of the participants in the studente movement, in UFG context, between 1979 and 1985, the last moments of Brazilian military dictatorship. That documentary focuses on reaction to images produced about and by youth college students at that time. The documentary will also deal with research of images and material documents. We will try to build an original soundtrack also genereted by sampling process, that is, sound reassembly of existing material. The soundtrack will be an element of expression and politica ideology. This work also proposes three new descriptive categories: micro power rizonomic network, visagem and symbolic accertion.